2012
DOI: 10.1088/0957-4484/23/9/095705
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties andin vitrobehavior of nanofiber–hydrogel composites for tissue engineering applications

Abstract: Hydrogel-based biomaterial systems have great potential for tissue reconstruction by serving as temporary scaffolds and cell delivery vehicles for tissue engineering (TE). Hydrogels have poor mechanical properties and their rapid degradation limits the development and application of hydrogels in TE. In this study, nanofiber reinforced composite hydrogels were fabricated by incorporating electrospun poly(ε-caprolactone) (PCL)/gelatin 'blend' or 'coaxial' nanofibers into gelatin hydrogels. The morphological, mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(108 citation statements)
references
References 19 publications
6
102
0
Order By: Relevance
“…Cells may be influenced by these materials either through contact or ingestion. The incorporation of electrospun nanofibres into hydrogels should increase the bulk elastic modulus and strength of these hydrogels [160,161] and can be used to dictate cell orientation and matrix production [160,162]. Nanofibres can be spun into aligned sheets that are then encapsulated by the cell-seeded hydrogels forming a nanofibre-cell-hydrogel composite.…”
Section: Rsfsroyalsocietypublishingorg Interface Focus 4: 20130038mentioning
confidence: 99%
“…Cells may be influenced by these materials either through contact or ingestion. The incorporation of electrospun nanofibres into hydrogels should increase the bulk elastic modulus and strength of these hydrogels [160,161] and can be used to dictate cell orientation and matrix production [160,162]. Nanofibres can be spun into aligned sheets that are then encapsulated by the cell-seeded hydrogels forming a nanofibre-cell-hydrogel composite.…”
Section: Rsfsroyalsocietypublishingorg Interface Focus 4: 20130038mentioning
confidence: 99%
“…However, significant reinforcement of the injectable gelatin was obtained when the electrospinning milled fibers were used to fabricate the composites (Figure 3-4b), as is noticeable by the change in the slope, which becomes higher with the increasing fiber content. A similar enhancement of the mechanical properties has been reported by other authors in systems that combine hydrogels and fibers [147], [150], [179]- [182], although the novel side to our system is the use of short fibers capable of being dispersed in an injectable hydrogel solution. The agglomeration of the high turbulent obtained fibers in the injectable gelatin solution prior to crosslinking may be causing the null reinforcement found here.…”
Section: Mechanical Propertiessupporting
confidence: 82%
“…121 However, it has been shown that such fibers can be effective as reinforcements for biomedical engineering purposes when combined with hydrogels. 124 . Manufacturing fibers in the nano scale is of great interest for composites, as these fibers have a high aspect ratio and large available fiber surface area, potentially leading to high in the design of tissue engineering scaffolds is to mimic the natural interfaces that interact selectively with a specific cell type through biomolecular recognition.…”
Section: Nanocompositesmentioning
confidence: 99%